STRUKTUR DAN MAKNA MANTRA UPACARA BALENGGANG DAYAK BAKATI’ RARA DESA MAYAK KECAMATAN SELUAS - Agustina, Delima; Seli, Sesilia; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This researcher is motivated by the idea of the importance of extracting oral literature (mantra). The general problem in this study is the environment of mantra imaging, mantra diction, rhyming mantra, meaning in mantra, and implementation plans for learning Indonesian. This research used descriptive method; the form of this research was qualitative and used a structural approach. The data source in this study was the informant who tells the mantra. The results were as follows. (1) The mantra imaging environment includes, areas and situations of using mantra in Balenggang rituals. (2) The rhymes used is full rhyme, absolute rhyme, and assonance rhyme. Absolute rhymes have 12 words, and rhymes with assonance are 4 words. Based on the location and line of sentences there are three rhymes, namely: initial rhymes have 3 words, middle rhymes have 5 words, and final rhymes have 3 words. (3) Common words in Balenggang mantra are 4 words, and special words in Balenggang mantra are 6 words. (4) The meaning of the mantra includes religious meaning (religious), social meaning and the meaning of personality (individual). (5) Balenggang mantra can be used as literary learning material in junior high school.  Key Words: Mantra Balenggang, Meaning, Structure.